Implikasi Hukum Terhadap Match Fixing Sepakbola Indonesia: Analisis Perbandingan Antara Hukum Perancis dan Jerman - Pangestu, Jevons; Gunawan, Indra Jaya (Fakultas Hukum Universitas Surabaya, 2023)
This research is intended to conduct a legal comparison between Indonesian law with French and German law regarding match fixing in football with the aim of studying the options whether the law in the two countries can be applied to our national law for the improvement of national law. This research is conducted with the type of normative legal research using secondary data in the form of primary legal materials and secondary legal materials obtained through literature study. The approach to conducting this norm comparison is included in the micro approach whose focus is the regulation of law. The method used in this research is the functional method, which means that in this research what is compared is the law as it functions and applies in a particular society in a particular place. The result and conclusion of this research find that Indonesia does not have specific regulations regarding match fixing in sports, especially football and Indonesia should be able to make “legal reforms” by regulating the application of the concept of private sector corruption, elements of prohibited actions such as accepting, giving, and requesting gifts, rewards, certain benefits for themselves or other parties that can affect the outcome or process of the match, as well as regulating more severe sanctions related to fines considering the motivation for committing match fixing crimes is financial gain with reference to French and German criminal law.